2017
DOI: 10.1016/j.cell.2017.09.039
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Inflammasome in Human Myeloid Cells Is Initiated by a STING-Cell Death Program Upstream of NLRP3

Abstract: SummaryDetection of cytosolic DNA constitutes a central event in the context of numerous infectious and sterile inflammatory conditions. Recent studies have uncovered a bipartite mode of cytosolic DNA recognition, in which the cGAS-STING axis triggers antiviral immunity, whereas AIM2 triggers inflammasome activation. Here, we show that AIM2 is dispensable for DNA-mediated inflammasome activation in human myeloid cells. Instead, detection of cytosolic DNA by the cGAS-STING axis induces a cell death program init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
434
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(489 citation statements)
references
References 54 publications
27
434
4
Order By: Relevance
“…Infection of IFNγ‐primed human THP1 cells with L. monocytogenes strain 10403S results in enhanced NLRP3 activation assisted by the IFNγ‐inducible GBP5 (Shenoy et al, ). Altogether, these studies are consistent with the recently identified AIM2‐independent, NLRP3‐dependent detection of cytosolic DNA in human, but not mouse, myeloid cells (Gaidt et al, ). This new DNA‐sensing pathway in human cells also requires lysosomal damage (Gaidt et al, ).…”
Section: Monocytogenes Benefits From Inflammasome Activationsupporting
confidence: 90%
See 1 more Smart Citation
“…Infection of IFNγ‐primed human THP1 cells with L. monocytogenes strain 10403S results in enhanced NLRP3 activation assisted by the IFNγ‐inducible GBP5 (Shenoy et al, ). Altogether, these studies are consistent with the recently identified AIM2‐independent, NLRP3‐dependent detection of cytosolic DNA in human, but not mouse, myeloid cells (Gaidt et al, ). This new DNA‐sensing pathway in human cells also requires lysosomal damage (Gaidt et al, ).…”
Section: Monocytogenes Benefits From Inflammasome Activationsupporting
confidence: 90%
“…Altogether, these studies are consistent with the recently identified AIM2‐independent, NLRP3‐dependent detection of cytosolic DNA in human, but not mouse, myeloid cells (Gaidt et al, ). This new DNA‐sensing pathway in human cells also requires lysosomal damage (Gaidt et al, ). Therefore, L. monocytogenes , plausibly via both LLO and release of DNA in the cytosol, activates the human NLRP3 inflammasome and the murine AIM2 inflammasome (Figure d).…”
Section: Monocytogenes Benefits From Inflammasome Activationsupporting
confidence: 90%
“…It is also important to highlight that most of the available data on the role of inflammasomes in epithelial cell immunity has been obtained using either human cell lines, or primary epithelial cells from mouse. Key differences between human and murine inflammasomes have already been described (for instance NLRC4 is not activated by the same components of bacterial flagellum in mouse and humans and DNA inflammasome activation in human monocytes depends on NLRP3 instead of AIM2). Therefore, more studies are needed in human lung epithelial cells to confirm the findings mentioned in this review.…”
Section: The Inflammasome: a Well‐regulated Immune Platform Also Presmentioning
confidence: 99%
“…The AIM2-like receptors (ALR), of which there are 4 in humans and 13 in mice, have in common a DNA-binding HIN domain and a Pyrin signaling domain. (63), The biologic role for all of these DNA sensors in vivo , aside from Cyclic GMP-AMP synthase (cGAS), has been questioned (64) and a recent study suggests that cGAS-STING, rather than AIM2 is responsible for inflammasome activation in myeloid cells (65). We will therefore focus on the sensor, cGAS.…”
Section: Nucleic Acids Stimulate Pattern Recognition Receptors To Indmentioning
confidence: 99%